Acute Abdomen in Pediatric Patients Admitted to the Pediatric Emergency Department - Yu-Ching Tseng; Ming-Sheng Lee; Yu-Jun Chang; Han-Ping Wu (Pediatrics and Neonatology)
Acute abdomen in children is a serious condition frequently encountered in the pediatric emergency department (ED). This study aimed to analyze the clinical spectrum of acute abdomen, and to investigate the prevalence of various etiologies in different age groups of children admitted to the pediatric ED. Methods: From 2005 to 2007, we retrospectively recruited 3980 consecutive pediatric patients who presented to the pediatric ED suffering from acute abdominal pain. Of these patients, 400 were identified as having acute abdomen. These patients were then divided into traumatic and non-traumatic groups, and also divided into four age groups: infant, preschool-age, school-age and adolescent. Differences between the traumatic and non-traumatic groups in the prevalence, clinical presentations, laboratory and imaging findings, and hospital courses were analyzed statistically. Results: In the non-traumatic group (n = 335), the most common etiology in infants was incarcerated inguinal hernia (14/31, 45.1%), followed by intussusception (13/31, 41.9%), while acute appendicitis was the major cause in children older than 1 year (68.7%). In the traumatic group (n = 65), the major cause of acute abdomen was traffic accidents (76.9%). The liver was the most frequently injured organ, followed by the spleen. The mortality rate was highest in patients with multiorgan injury. In both groups, bowel loop dilation and local ileus were the two most common findings demonstrated by plain film X-rays. Children in the traumatic group who underwent abdominal computed tomography (CT) scans all showed positive findings for their diagnoses. Patients with bowel perforation or obstruction had the longest durations of hospitalization in the non-traumatic group, while those with multiorgan injury had the longest duration in the traumatic group. Conclusion: The etiology of acute abdomen varied depending on the age of the patient. Acute appendicitis was the most common cause of acute abdomen in children older than 1 year of age, followed by traumatic injury. Abdominal CT scanning was a useful diagnostic imaging modality in patients with both traumatic and non-traumatic abdominal pain.